Management of thoracic outlet syndrome. - Dale, W A (1975)
This overall management program for thoracic outlet compression syndrome is based upon experience with 153 extremities in 149 patients and the results of others. The following conclusions are documented and discussed. 1) Diagnosis is based chiefly upon history; physical signs are inconstant and often absent. 2) Major vascular problems are unusual; angiography is not always necessary. 3) Electromyography is not always critical but does aid in diagnosis of carpal tunnel syndrome. 4) Non-operative treatment relieves most patients; operative decompression is indicated for a minority. 5) Transxillary first rib resection, with removal of cervical rib is the best operation. 6) Carpal tunnel decompression should be done concomitantly when needed. 7) Operation is relatively safe.